GEOPOLITICAL RISK ON STOCK RETURNS: EVIDENCE ON THE ROLE OF OIL PRICES IN ASEAN MARKETS - Safirussalim; Ramadhan, Muhammad Afi (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2026)
Purpose – This study examines how geopolitical risk affects stock returns and market volatility in ASEAN countries during the early 2026 geopolitical tension period. Methods – Using daily data from five ASEAN stock markets, the study analyzes 290 observations through panel regression, robustness testing, and GARCH modelling. Geopolitical risk is measured using the Geopolitical Risk index, while oil returns and exchange rates are included as explanatory variables. Findings – Geopolitical risk has a negative and statistically significant effect on stock returns (β = −0.0000212; p = 0.045), although its economic magnitude is relatively small. Oil returns show a stronger negative effect (β = −0.0871; p = 0.005), indicating that energy price movements are more strongly associated with ASEAN market responses. Research implications – The findings suggest that investors and policymakers should pay closer attention to energy-price movements when assessing financial market vulnerability during geopolitical uncertainty. Originality – This study contributes event-window evidence from ASEAN markets by combining geopolitical risk, oil returns, exchange rates, and GARCH-based volatility analysis.